2003
DOI: 10.1097/00002030-200306130-00008
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with atazanavir plus saquinavir in patients failing highly active antiretroviral therapy: a randomized comparative pilot trial

Abstract: In antiretroviral-experienced patients, once-daily atazanavir/saquinavir was safe and well tolerated, showing comparable efficacy to twice-daily ritonavir/saquinavir, both with two NRTIs. Small lipid changes from baseline with atazanavir/saquinavir were not clinically significant in comparison with the prompt, marked and sustained changes of a magnitude suggesting clinical relevance achieved in the ritonavir/saquinavir group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 21 publications
2
62
0
1
Order By: Relevance
“…In order to set up an experimental model to study the HAART-associated lipodystrophy, control mice were compared to mice receiving two long-term intraperitoneal treatments: treatment with the classical combination of LPV/r, which is strongly involved in HAART, and treatment with the new compound ATV, which induces rare metabolic disorders in patients (12,19).…”
Section: Resultsmentioning
confidence: 99%
“…In order to set up an experimental model to study the HAART-associated lipodystrophy, control mice were compared to mice receiving two long-term intraperitoneal treatments: treatment with the classical combination of LPV/r, which is strongly involved in HAART, and treatment with the new compound ATV, which induces rare metabolic disorders in patients (12,19).…”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical studies in patients (Woerle et al, 2003;Calza et al, 2004) and in normal subjects (Purnell et al, 2000;Noor et al, 2002Noor et al, , 2004 have confirmed a direct connection between some protease inhibitors and metabolic effects, despite the complexity of multidrug therapy and virological and immunological responses during HAART. The recent emergence of a newer generation of protease inhibitor that exhibits antiviral efficacy without adverse affects on lipid or glucose parameters in the clinic (Haas et al, 2003;Murphy et al, 2003;Sanne et al, 2003;Cahn et al, 2004;Noor et al, 2004;Squires et al, 2004) provided an opportunity to reexamine the molecular pharmacology and toxicology of the protease inhibitor class.…”
mentioning
confidence: 99%
“…Reports of adverse effects were similar when ATV plus SQV was compared to SQV plus low-dose RTV. 43 Yet, significantly more patients discontinued treatment early due to adverse reactions in the SQV plus low-dose RTV group. Atazanavir's most notable laboratory abnormality is indirect hyperbilirubinemia, which is reversible upon discontinuation.…”
Section: Adverse Drug Reactionsmentioning
confidence: 97%
“…One study in treatment-experienced adults showed similar efficacy between once-daily ATV plus saquinavir (SQV) compared to twice-daily SQV plus low-dose RTV when administered as part of combination therapy. 43 Information regarding the antiretroviral efficacy of ATV is not yet available in pediatric patients < 16 years of age.…”
Section: Efficacymentioning
confidence: 99%